Pengaruh Ketepatan Waktu Terhadap Pendistribusian Barang Di Unit Logistik UPT. Balai Yasa Pulubrayan - Khotiza Anisa; Nuri Aslami (LPPM Universitas Labuhanbatu, 2022)
The greater the intensity of business competition to attract industrial consumers, the more sensitive industrial customers are to the quality of services or goods provided by service providers. Logistics is essential to achieving competitive advantage in most product-oriented companies. This research is aimed at customers and also focused on companies, namely on how physical distribution managers can measure the value they provide to customers. Physical or logistical distribution is described as the process of organizing the transfer of commodities from suppliers or vendors to internal operations, i.e. warehouse and transportation management. The purpose of this study to determine the impact of warehousing management system on the smooth distribution. Research data collection was conducted using observation, interviews, and literature studies. The results of this study reveal that there is a significant and strong impact between the timeliness of the distribution of goods in the logistics unit UPT. Pulubrayan Yasa Hall.Â